Dynamics around non-spherical symmetric bodies - I. the case of a spherical body with mass anomaly - Madeira, G. [UNESP]; Giuliatti Winter, S. M. [UNESP]; Ribeiro, T. [UNESP]; Winter, O. C. [UNESP] (Oxford University Press (OUP), 2022)
The space missions designed to visit small bodies of the Solar system boosted the study of the dynamics around non-spherical bodies. In this vein, we study the dynamics around a class of objects classified by us as non-spherical symmetric bodies, including contact binaries, triaxial ellipsoids, and spherical bodies with a mass anomaly, among others. In this work, we address the results for a body with a mass anomaly. We apply the pendulum model to obtain the width of the spin-orbit resonances raised by non-asymmetric gravitational terms of the central object. The Poincare surface of section technique is adopted to confront our analytical results and to study the system's dynamics by varying the parameters of the central object. We verify the existence of two distinct regions around an object with a mass anomaly: a chaotic inner region that extends beyond the corotation radius and a stable outer region. In the latter, we identify structures remarkably similar to those of the classical restrict and planar three-body problem in the Poincare surface of sections, including asymmetric periodic orbits associated with 1:1+p resonances. We apply our results to a Chariklo with a mass anomaly, obtaining that Chariklo rings are probably related to first kind periodic orbits and not with 1:3 spin-orbit resonance, as proposed in the literature. We believe that our work presents the first tools for studying mass anomaly systems.
Keywords: celestial mechanics; Kuiper belt objects: individual: (10199) Chariklo; minor planets, asteroids: general; planets and satellites: dynamical evolution and stability; planets and satellites: rings